Concentration‐Discharge Relationships of Dissolved Rhenium in Alpine Catchments Reveal Its Use as a Tracer of Oxidative Weathering. Issue 11 (23rd November 2021) - Hilton, Robert G.; Turowski, Jens M.; Winnick, Matthew; Dellinger, Mathieu; Schleppi, Patrick; Williams, Kenneth H.; Lawrence, Corey R.; Maher, Katharine; West, Martin; Hayton, Amanda
Abstract: Oxidative weathering of sedimentary rocks plays an important role in the global carbon cycle. Rhenium (Re) has been proposed as a tracer of rock organic carbon (OCpetro ) oxidation. However, the sources of Re and its mobilization by hydrological processes remain poorly constrained. Here, we examine dissolved Re as a function of water discharge, using samples collected from three alpine catchments that drain sedimentary rocks in Switzerland (Erlenbach and Vogelbach) and Colorado, USA (East River). The Swiss catchments reveal a higher dissolved Re flux in the catchment with higher erosion rates, but have similar [Re]/[Na + ] and [Re]/[SO4 2− ] ratios, which indicate a dominance of Re from OCpetro . Despite differences in rock type and hydro‐climatic setting, the three catchments have a positive correlation between river water [Re]/[Na + ] and [Re]/[SO4 2− ] and water discharge. We propose that this reflects preferential routing of Re from a near‐surface, oxidative weathering zone. The observations support the use of Re as a proxy to trace rock‐organic carbon oxidation, and suggest it may be a hydrological tracer of vadose zone processes. We apply the Re proxy and estimate CO2 release by OCpetro oxidation of 5.7 +6.6 /−2.0 tC km −2  yr −1 for the Erlenbach. The overall weathering intensity was ∼40%, meaning that the corresponding export of unweathered OCpetro in river sediments is large, and the findings call for more measurements of OCpetro oxidation in mountains and rivers as they cross floodplains. Plain Language Summary: When rocks undergo chemical weathering, breakdown of organic matter that has been stored in the rocks over time can release carbon dioxide to the atmosphere. It has remained a challenge to track and quantify this process, but the element rhenium provides a tool to do this. When organic matter in rocks undergoes oxidative weathering, rhenium is oxidized and enters river water. We can use measurements of dissolved rhenium fluxes as a proxy to estimate rock organic carbon oxidation. However, we still lack information on the sources of rhenium in river catchments and need a better understanding of the pathway that rhenium takes from rocks, through soils into streams and rivers. Here, we measured dissolved rhenium alongside other weathering products in three catchments that drain alpine landscapes made up of sedimentary rocks. The catchments behave in a remarkably similar way, where the relative amount of rhenium in river water increases with water flow. Based on our ideas of how water moves through the landscape, our results suggest that rhenium is moved from a near‐surface zone in all three catchments, where oxygen and rock organic carbon react. By applying the proxy to the catchments, we confirm that oxidative weathering rates and their carbon dioxide release increase with physical erosion rates. Key Points: We explore the mobility of rhenium in three alpine catchments, in the context of its use as a proxy for rock organic carbon oxidation The relative abundance of dissolved Re increases with discharge, explained by a model where Re is mobilized from near surface zone The findings support rhenium as a proxy for oxidative weathering, and we find rock organic carbon oxidation increases with erosion rate